Chimeric Antigen Receptor T-Cell Therapy for B-Cell Acute Lymphoblastic Leukemia: Current Landscape in 2021. Issue 2 (March 2021) - Gauthier, Jordan; Turtle, Cameron J.
Abstract : Abstract: Immunotherapy with T cells engineered to express a chimeric antigen receptor (CAR T cells) is reshaping the management of patients with relapsed or refractory B-cell malignancies. High efficacy of CD19-targeted CAR T cells has been reported in children and adults with B-cell acute lymphoblastic leukemia (B-ALL), with complete responses without detectable minimal residual disease occurring in approximately 80% to 90% of patients. This led to the approval of tisagenlecleucel (Kymriah) by the Food and Drug Administration based on the results of the ELIANA trial. Although CD19 CAR T-cell therapy may be curative in children, responses are short-lived in most adult B-ALL patients. In addition, CAR T-cell therapy can be associated with severe, potentially life-threatening, toxicities, such as cytokine release syndrome and immune effector cell–associated neurotoxicity syndrome. Here, we review the recent advances in CAR T-cell therapy for R/R B-ALL and discuss strategies to improve its efficacy while minimizing toxicities.